2017
DOI: 10.1111/desc.12579
|View full text |Cite
|
Sign up to set email alerts
|

Differences in brain morphology and working memory capacity across childhood

Abstract: Working memory (WM) skills are closely associated with learning progress in key areas such as reading and mathematics across childhood. As yet, however, little is known about how the brain systems underpinning WM develop over this critical developmental period. The current study investigated whether and how structural brain correlates of components of the working memory system change over development. Verbal and visuospatial short‐term and working memory were assessed in 153 children between 5.58 and 15.92 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 119 publications
2
38
0
Order By: Relevance
“…Furthermore, we hypothesize that this system is mainly governed subcortically early in development. It also seems possible that early imitation processes rely more on distributed networks while later imitation will rely on more specialized circuitry as recently found for the development of working memory (Bathelt, Gathercole, Johnson, & Astle, 2017). Associative learning seems less plausible as an explanation of imitation in newborns, although it probably comes into play as a child's imitative ability or motivation to imitate develops over time.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, we hypothesize that this system is mainly governed subcortically early in development. It also seems possible that early imitation processes rely more on distributed networks while later imitation will rely on more specialized circuitry as recently found for the development of working memory (Bathelt, Gathercole, Johnson, & Astle, 2017). Associative learning seems less plausible as an explanation of imitation in newborns, although it probably comes into play as a child's imitative ability or motivation to imitate develops over time.…”
Section: Discussionmentioning
confidence: 96%
“…Early childhood is a period of profound maturation of cognitive and behavioral skills, including attention (Breckenridge et al, 2013;Mullane et al, 2016), working memory (Burnett Heyes et al, 2012), reading (Ferretti et al, 2008), math (Garon-Carrier et al, 2018), and self-regulation (Montroy et al, 2016). These skills have been linked to white matter properties during childhood (Bathelt et al, 2018;Jolles et al, 2016;Klarborg et al, 2013;Qiu et al, 2008;Van Eimeren et al, 2008), though the relationship between cognitive-behavioral skills and axonal density and fiber bundle size remains largely unexplored. One study has shown an association between FD and inattentive/internalizing behavior in typically developing children (Genc et al, 2019), while we have previously reported an association between FD and social skills in adolescents and young adults with Autism Spectrum Disorder .…”
Section: Cognitive-behavioral and Functional Relevancementioning
confidence: 99%
“…Maturation of these essential cognitive-behavioral skills is believed to be related to white matter growth in the brain (Bathelt et al, 2018;Jolles et al, 2016;Klarborg et al, 2013;Qiu et al, 2008;Van Eimeren et al, 2008), though developmental trajectories of white matter maturation and the biological underpinnings of these changes remain poorly understood. The reason for this is two-fold.…”
Section: Introductionmentioning
confidence: 99%
“…Axonal fiber bundles (also referred to as “white matter tracts”) form the structural framework of the brain, facilitating rapid communication across brain networks and enabling distributed cognitive processing. Developmental changes in white matter properties are unsurprisingly linked to cognitive maturation (Bathelt et al, 2018; Jolles et al, 2016; Klarborg et al, 2013; Qiu et al, 2008; Van Eimeren et al, 2008), though these changes are understudied during early childhood, and trajectories for specific structural features are unclear.…”
Section: Introductionmentioning
confidence: 99%